Remote patient monitoring - Anannya Gupta (Journal of Applied Sciences and Clinical Practice, 2023)
Concerns about the unsatisfactory condition of chronic disease management prompted the design and development of a telemonitoring home system based on user input. Patients, caring for themselves through self-care and monitoring, can control and prevent chronic disorders, restructuring the treatment process into a constant cooperative interaction between patients and health-care professionals. The primary major goal of this study is to highlight future research directions in remote health care and patient monitoring for chronic illnesses treatment and management, as well as to provide an overview of the current state of remote patient monitoring (RPM), its contemporary constraints, and possible future prospects that will aid to resolve those contemporary constraints. The methodology of this review is that an independent literature search was conducted on Medline, PubMed, and Google Scholar for the below-mentioned keywords, and studies published till April 2022 that had used any type of RPM intervention were screened for inclusion in the review. The conclusion of this review is that continuous RPM may increase patient adherence to medication and other guideline-recommended therapy strategies that have been linked to a reduction in clinical mortality and better prognosis. However, a number of technological, medical legal and economic barriers must be overcome before they may be widely used.